2022
DOI: 10.3389/fmicb.2022.892447
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RNA in Wastewater Was Highly Correlated With the Number of COVID-19 Cases During the Fourth and Fifth Pandemic Wave in Kobe City, Japan

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of the current coronavirus disease 2019 (COVID-19) pandemic and associated respiratory infections, has been detected in the feces of patients. Therefore, determining SARS-CoV-2 RNA levels in sewage may help to predict the number of infected people within the area. In this study, we quantified SARS-CoV-2 RNA copy number using reverse transcription quantitative real-time PCR with primers and probes targeting the N gene, which allows the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…2 b). The concentration range of SARS-CoV-2 in wastewater observed in the present study is consistent with those from previous studies in Japan ( Ando et al, 2022 ; Hata et al, 2021 ; Kitamura et al, 2021 ; Wang et al, 2022 ; Tanimoto et al, 2022 ). No significant correlations were observed between SARS-CoV-2 titers in grab and composite samples ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…2 b). The concentration range of SARS-CoV-2 in wastewater observed in the present study is consistent with those from previous studies in Japan ( Ando et al, 2022 ; Hata et al, 2021 ; Kitamura et al, 2021 ; Wang et al, 2022 ; Tanimoto et al, 2022 ). No significant correlations were observed between SARS-CoV-2 titers in grab and composite samples ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…The correlation between viral RNA in wastewater and disease cases, as well as the capability of WBS to predict cases, has also been shown with other viruses in addition to RSV. Multiple studies have shown that the amount of SARS-CoV-2 RNA in wastewater is correlated with the number of COVID-19 disease cases. The correlation between wastewater and clinical cases has also been found for the influenza virus. ,, In Finland in the same WWTPs, the correlation coefficient of influenza A RNA in wastewater and the incidence of influenza A (CC = 0.427–0.870) were shown to be similar to the RSV correlation measured in our study (CC = 0.412–0.865) . The study was conducted using the same WWTPs used in this study.…”
Section: Resultssupporting
confidence: 84%
“…The correlation between viral RNA in wastewater and disease cases, as well as the capability of WBS to predict cases, have also been shown with other viruses, in addition to RSV. Multiple studies have shown that the amount of SARS-CoV-2 RNA in wastewater is correlated with the number of COVID-19 disease cases (Acosta et al, 2023; Tanimoto et al, 2022; Wani et al, 2023; Wolfe et al, 2021; Zhan et al, 2022). The correlation between wastewater and clinical cases has also been found for the influenza virus (Boehm et al, 2022; Wolfe et al, 2022; Wolken et al, 2023).…”
Section: Resultsmentioning
confidence: 99%